Do regional payroll tax reductions boost employment? - Helge Bennmarker; Erik Mellander; Björn Öckert (Institute for Labour Market Policy Evaluation (IFAU), 2008)
Using a Difference-in-Differences approach we evaluate the effects of a 10 percentage points reduction in the payroll tax introduced in 2002 for firms in the northern part of Sweden. We find no employment effects for existing firms and can rule out that a 1 percentage point payroll tax reduction would increase employment with more than 0.2 percent. We do, however, find that tax reductions have significantly positive effects on the average wage bill per employee. These are likely to be driven by higher average wages, but might also be due to more hours worked. As a sensitivity check we investigate if reduced payroll taxes affect the likelihood of firm entry and exit, and find some support for a net firm inflow. Our attempts to assess concomitant effects on employment indicate that payroll tax reductions might yield increases in employment through the start-up of new firms.
Keywords: H22; J23; J38; J58; J68; 330; Payroll tax; labour demand; incidence; firm entry/exit; difference-in-differences; Lohnsummensteuer; Arbeitsnachfrage; Steuerinzidenz; Markteintritt; Marktaustritt; Schweden